Access and success in higher education in Portugal: issues of gender, sociocultural origin and students' academic path / Acesso e sucesso no Ensino Superior em Portugal: questões de género, origem sócio-cultural e percurso académico dos alunos - Leandro S. Almeida; M. Adelina Guisande; Ana Paula Soares; Luísa Saavedra (Psicologia: Reflexão e Crítica, 2006)
We analyse the impact of gender and sociocultural origin of freshmen from their college entrance exam scores and chosen undergraduate courses, as well the anticipation of difficulties in academic adaptation, and in academic success, at the end of their first year in college. The study's sample consists of 1407 freshman students from the Universidade do Minho. Results show that gender and sociocultural family background influence the courses that are chosen (most female students and students from less advantaged social class origins attended Social Science courses, whereas most male students and students from more advantaged social class origins attended Engineering courses). Higher sociocultural status and female students presented higher entrance exam scores and averaged better academic achievement at the end of their first year in college. Concerning anticipated difficulties, female students and students from Social and Economic Science courses anticipated more inter-personal difficulties, while male students and students from Engineering and Economic Science courses anticipated more difficulties in relation to learning and organizing daily activities. The anticipation of learning difficulties was associated in a negative and statistical way with entrance exam scores and academic achievement.